Letterkunde as kulturele ekologie in Die Bergengel (Carina Stander) - Susan Meyer (Tydskrif vir Letterkunde, 2019)
Die Bergengel (The Angel of the Mountain), with its striking nature centeredness, is characterised by poetical and lyrical use of language. This aspect is drawn into the ecocritical study of the novel in this article. Hubert Zapf’s theory on literature as cultural ecology, placed within the theoretical frame of material ecocriticism, supplies the foundation for this study. An ecocritical reading of Die Bergengel leads to uncovering a counter-discourse in the novel aimed at disrupting prevalent anthropocentric views on nature and environmental issues. Narrative events reveal the agentic power of nature and its dynamic influence on human conditions; the novel challenges the long taken-for-granted dominant position of humankind. The poetic language effectively functions in highlighting the interconnections between different forms of life where previously we had seen separations, suggesting more thoughtful interpretations of human-nonhuman-relations underlying the practices of environmental violence and exploitation the novel speaks of. Where the play with language and words is so directly connected with the ecocritical discourse, literature’s potential in bringing together the supposed separated spheres of culture (language) and nature becomes clear. Die Bergengel cogently voices the idea of the “reintegrative interdiscourse” which is central to Zapf’s viewing of literature as cultural ecology.